Diseño objetual; nuevas aportaciones (1997)
Alfombras Gandia Blasco, V.Gallén; Sistema Compás (asientos modulares, M.Ciganda; Colecciones Sabana y Flavia (objetos), S.Diaz; Librería Prologo (estanterias), J.Tresserra; Colección de alfombras La Granja, M.Duran; Lámpara Veroca, M.Ciganda
Keywords: DISEÑO; DISEÑO DE INTERIORES; DISEÑO INDUSTRIAL; DISEÑO TEXTIL